ANALISIS EFEKTIFITAS PERATURAN DAERAH KOTA MATARAM NOMOR 15 TAHUN 2003 TENTANG GARIS SEMPADAN SUNGAI TERHADAP PENGENDALIAN PEMBANGUNAN - RAMLI RAMLI; I PUTU PASEK BAGIARTHA W; IMAM EDY ASHARI (Universitas Mahasaraswati Mataram, 2018)
The purpose of this study is to determine the factors that caused the community to establish settlements on the riverbanks, the impact of settlements on the riverbanks and the effectiveness of the Local Regulation Policy No. 15 of 2003 concerning the river boundary line for development control.The results show that: 1). The policy and implementation of the Mataram City Regulation, Number 15 of 2003 concerning settlements on riverbanks is less effective, 2). The impact of settlements on the riverbanks / riverbanks is: The body of river is getting narrower, the reduction of clean water sources and the occurrence of euritification which cause losses, among others, complicate irrigation and transportation facilities and are less attractive if developed for tourism areas.. 3) Factors affecting the settlement at the edge of the river are: a). Increasing population movement from village to city or commonly called urbanization, as happened in the city of Mataram resulted in population density until settlement problems arose, including settlements along the riverbanks, b). The ignorance of the public that there is a prohibition and legal sanction to build buildings by the river, c). The socio-economic conditions of the people who build houses on the riverbanks are generally low d). Lack of knowledge and legal awareness from the community, e). Limited land availability and high land prices, f). Legal supervision and sanctions have not been carried out according to the rules.